Methodology of Scientific Cognizance - Nguyen Anh Quoc; Nguyen Minh Tri (MultiTech Publisher, 2024)
Methodology in scientific research is essential. Each science has its own object, and different methodologies cause and result in different perceptions. Science is human life, however, science becomes metaphysical theory because it is conditioned by the methodology of philosophy or mathematics. Philosophy and mathematics are theoretical sciences, which makes the related sciences dream, ideal, and science fantasy. The helplessness of science becomes man's misfortune, science becomes alien to man. True science begins with real people living, that is human science. Human science becomes the methodology in the study of related sciences. When studying the outside world, people uphold the principles of objectivity, comprehensiveness, development, specific history, and research practice. When studying life, the perceived object begins to die from the real person, in the process, people always create possibilities and needs. The transformation between abilities, needs means and goals makes life rich and diverse. Humans are both subjects and objects of scientific research. The interdisciplinary sciences have in common that they take human activities as research objects.